2012
DOI: 10.1155/2012/895326
|View full text |Cite
|
Sign up to set email alerts
|

Improving Total-Cholesterol/HDL-Cholesterol Ratio Results in an Endothelial Dysfunction Recovery in Peripheral Artery Disease Patients

Abstract: Aims. To evaluate the effects of variations of total-cholesterol/HDL-cholesterol ratio and the effects of the atorvastatin on endothelial function in peripheral artery disease (PAD). Material and Methods. A prospective, randomised controlled study was carried out in 150 PAD patients. Patients randomized to the control group (n = 75) were treated with antiplatelet drugs, angiotensin-converting-enzyme inhibitors and cardiovascular-risk-factor control. Experimental group (n = 75) also received treatment with ator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
0
14
0
3
Order By: Relevance
“…A recent study had demonstrated that patients with peripheral artery disease treated with atorvastatin showed improvement in endothelial function and this was associated with decreased TC/HDL ratio, suggesting that this ratio may relate to endothelial damage 72.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study had demonstrated that patients with peripheral artery disease treated with atorvastatin showed improvement in endothelial function and this was associated with decreased TC/HDL ratio, suggesting that this ratio may relate to endothelial damage 72.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also suggested that the non-HDL-C/HDL-C ratio is a better marker than the apoB/apoA1 ratio for identifying IR and MetS in Koreans (71). A recent study had demonstrated that patients with peripheral artery disease treated with atorvastatin showed improvement in endothelial function and this was associated with decreased TC/ HDL ratio, suggesting that this ratio may relate to endothelial damage (72).…”
Section: Discussionmentioning
confidence: 99%
“…Part of the atheroprotective effect is associated with the transport of excess cholesterol deposited in the blood vessels to the liver (Bleda et al, 2012). The effects of antioxidants inhibit the oxidation of cholesterol in the blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of diabetic ulcer patients in Indonesia is around 15%. The case of diabetic ulcers is often the result of late manifestations of peripheral neuropathy, Peripheral Arterial Disease (PAD) or a combination of both (Brownrigg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Decrease in the level of total-cholesterol/HDL-cholesterol ratio and HDL-cholesterol/LDLcholesterol ratio is linked to a reduction in the risk of morbidity and mortality in cardiovascular diseases [32]. Endothelial cells appear to regulate the trafficking and release of HSCs from bone marrow [33].…”
Section: Discussionmentioning
confidence: 99%